2018
DOI: 10.1371/journal.pone.0194624
|View full text |Cite
|
Sign up to set email alerts
|

Predation risk landscape modifies flying and red squirrel nest site occupancy independently of habitat amount

Abstract: Habitat choice often entails trade-offs between food availability and predation risk. Understanding the distribution of individuals in space thus requires that both habitat characteristics and predation risk are considered simultaneously. Here, we studied the nest box use of two arboreal squirrels who share preferred habitat with their main predators. Nocturnal Ural owls (Strix uralensis) decreased occurrence of night-active flying squirrels (Pteromys volans) and diurnal goshawks (Accipiter gentilis) that of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 84 publications
2
21
1
Order By: Relevance
“…Red squirrels do well in human-dominated areas (e.g. Fey et al 2016, Jokimäki et al 2017, Turkia et al 2018a, where they find alternative food resources provided by humans. Pine martens have not yet settled to urban areas in Finland, and goshawks mainly visit urban areas in the winter (Vuorisalo et al 2003), although goshawks have recently also started to thrive near to and within cities (Solonen 2008).…”
Section: Bottom-up and Top-down Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Red squirrels do well in human-dominated areas (e.g. Fey et al 2016, Jokimäki et al 2017, Turkia et al 2018a, where they find alternative food resources provided by humans. Pine martens have not yet settled to urban areas in Finland, and goshawks mainly visit urban areas in the winter (Vuorisalo et al 2003), although goshawks have recently also started to thrive near to and within cities (Solonen 2008).…”
Section: Bottom-up and Top-down Effectsmentioning
confidence: 99%
“…Previous studies suggest that the effect of goshawks on red squirrels is not straightforward, but may vary depending on other factors than mere abundances of predator and prey. For example, Turkia et al (2018a) found support for habitat-specific predation by goshawks, whereby goshawks affected red squirrel occurrence most negatively in a mutually non-preferred habitat. Locally, predator avoidance can affect space use of red squirrels, but on a larger scale, common habitat preferences arise as the dominant phenomena causing positive correlation between their abundances.…”
Section: Bottom-up and Top-down Effectsmentioning
confidence: 99%
“…However, this hypothesis seems unlikely in our case (see also Fey et al, 2016) because the amount of unpreferred habitat along the dispersal routes did not affect dispersal distances. We think the association with edges observed in this study simply reflects the preference for edge habitats in our study areas (Turkia et al, 2018).…”
Section: Discussionmentioning
confidence: 56%
“…Perhaps this result reflects individuals spending time and/or moving along edges (see e.g., Latham, Latham, Boyce, & Boutin, ). Indeed, earlier studies have observed that red squirrels may prefer edge habitats (Dylewski, Przyborowski, & Myczko, ; Turkia, Korpimäki, Villers, & Selonen, ). In the case of the red squirrel, the reason to spend time at forest edges may be due to the possibly larger cone production of spruces growing on edges and getting more light for their growth (Dylewski et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Proximity to human settlements and human disturbance influenced chimpanzees relatively less than gorillas (Figures 4 and 6), indicating that chimpanzees may experience a trade‐off between finding fruits and avoiding perceived predation risk. This trade‐off has been documented in wildebeests (M'Soka et al, 2017) and red squirrels (Turkia, Korpimaki, Villers, & Selonen, 2018). If a species experiences a trade‐off between access to a resource and predation risk, it may avoid predation or areas of high predation risk when it has an alternative area in which to find food (Frid & Dill, 2002).…”
Section: Discussionmentioning
confidence: 89%